O podcast como uma nova mídia: Um estudo sobre o Flow Podcast - Paulo Henrique Morais Coluti (2025)
This dissertation investigates the evolution of the podcast as a communication medium, focusing on its transition into an audiovisual format. Given that the phenomenon has incorporated a visual dimension, the study questions its current definition, as traditional classifications emphasize its auditory nature. The research adopts a theoretical approach based on the concepts of McLuhan, Lévy, Dizard Jr., Manovich, and Jenkins, among others, exploring orality, collective intelligence, new media, and the evolution of digital technologies. Methodologically, the dissertation moves away from classical approaches, opting for an empirical analysis of selected episodes of the Flow Podcast. The study examines five emblematic episodes to highlight audiovisual integration. The episode analysis was complemented by a questionnaire, allowing an assessment of their media characteristics, consumption format, and the applicability of the presented theories. The results indicate an evolution toward a hybrid format - making the distinction between podcasts and videocasts unnecessary - where the presence of video not only complements but redefines its identity. Visual interaction, setting, and language play a crucial role in the audience’s experience. This study contributes to the understanding of the podcast not merely as a distribution format but as a new medium, whose identity is shaped by technology and contemporary production and consumption dynamics.